The Adat Aceh: A window into a 17th-century Malay soundscape. Issue 145 (2nd September 2021) - Halid, Raja Iskandar Bin Raja
ABSTRACT: After the fall of Melaka to the Portuguese in 1511, Aceh began to assert itself as a formidable Malay sultanate. After annexing Pasai and its neighbouring polities in 1524, Aceh gradually replaced Melaka as the centre of the Malay world. The Aceh sultanate held elaborate ceremonies and celebrations, which involved the playing of music in street processions as part of its royal adat or customs. This was seen as an important visual and aural representation of the ruler's authority and presence towards not only its people and other regional sultanates, but also foreign visitors. The nobat, a court musical ensemble, was central to a Malay royal institution, revered for its mystical powers and ability to consolidate and maintain socio-political order. The use of the nobat and other instruments in the Acehnese court ceremonies was documented in a 17th-century text called the Adat Aceh (Customs of Aceh). This article looks into the text and its musical content, supported by European accounts, in analysing the important role of music in the adat and istiadat of the Acehnese court.